2012
DOI: 10.1007/s10980-012-9782-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of changing climate and land use on vegetation dynamics in a Mediterranean ecosystem: insights from paleoecology and dynamic modeling

Abstract: Forests near the Mediterranean coast have been shaped by millennia of human disturbance. Consequently, ecological studies relying on modern observations or historical records may have difficulty assessing natural vegetation dynamics under current and future climate. We combined a sedimentary pollen record from Lago di Massacciucoli, Tuscany, Italy with simulations from the LANDCLIM dynamic vegetation model to determine what vegetation preceded intense human disturbance, how past changes in vegetation relate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 54 publications
(80 reference statements)
6
86
0
1
Order By: Relevance
“…Forest composition simulated for the last 7,000 y in northern Italy, using temperature as the climate forcing, showed that moderate climate change during the Holocene could not explain the dramatic decline of Abies alba and increase in evergreen oaks detected in the pollen record (119). The observed vegetation changes could only be simulated when increased grazing and frequent fires, associated with Neolithic human settlement, were included in the model.…”
Section: Accounting For Dispersal Limitations When Predicting Speciesmentioning
confidence: 95%
“…Forest composition simulated for the last 7,000 y in northern Italy, using temperature as the climate forcing, showed that moderate climate change during the Holocene could not explain the dramatic decline of Abies alba and increase in evergreen oaks detected in the pollen record (119). The observed vegetation changes could only be simulated when increased grazing and frequent fires, associated with Neolithic human settlement, were included in the model.…”
Section: Accounting For Dispersal Limitations When Predicting Speciesmentioning
confidence: 95%
“…For example, declining summer precipitation indicates a trend toward increased seasonality: many places that were moderately or weakly seasonal showed downward trends in summer precipitation, with less precipitation today than in previous decades. This suggests that summers are becoming more harsh, which may cause a shift toward aquatic and terrestrial ecosystems better suited to strongly seasonal conditions [66,67]. Equally significant, downward trends in annual precipitation but not FWS precipitation suggest that precipitation is not declining during the rainy season, but rather during other times of year-possibly during early fall and late spring.…”
Section: Trendsmentioning
confidence: 99%
“…During early Medieval times (ad 700-800), pollen records suggest land-use intensification in the Mediterranean realm (Atherden and Hall, 1999;Colombaroli et al, 2007;Sobrino et al, 2005). Constant grazing and frequent burning eliminated forests and favoured the expansion of garrigue and maquis (Henne et al, 2013;Tinner et al, 2009). Human disturbance in the Mediterranean is often related to burning (Colombaroli et al, 2008;Moreno et al, 1998;Vannière et al, 2011), but the lack of information about palaeo-fire activity on Pantelleria impedes an assessment of the long-term relevance of fire for the island.…”
Section: Introductionmentioning
confidence: 99%